Chemistry and industrial and environmental governance in France, 1770–1830. (June 2016) - Le Roux, Thomas
This article examines how chemists contributed to the technological reorganization in France at the end of the eighteenth century and the beginning of the nineteenth century, how they justified using potentially harmful or polluting processes by stating that this would contribute to national prosperity, and how the idea of improvement helped to legally and rhetorically build a production regime that disqualified traditional precautionary attitudes to certain artisanal and industrial processes. This resulted in the establishment of a new environmental governance regime devoted to the advancement of chemistry and of industrial production. While this shift was clearly perceptible from the 1770s with the first regulatory exceptions for strategic products, the 1810 decree, which was imagined, designed, and implemented by chemists, perpetuated chemistry's role as an environmental regulator.